Pengaruh Karakteristik Dewan Komisaris Terhadap Kemampuan Memprediksi Financial Distress: Studi pada Perusahaan BUMN - Frans Dika Permana; Vanica Serly (Universitas Negeri Padang, 2021)
This research aims to analysis the effect size of board commissioners, independent commissioners, competence of board commissioners and meeting frequency of board commissioners on financial distress. The data in study are annual report of BUMN companies in Indonesian registered at the ministry BUMN in 2015 – 2019. This research using purposive sampling method obtained by 175 sample from 35 companies conducted observations from 2015 – 2019, the hypothesis testing in this research using multiple linear regression analysis. The result of this research showed that the independent commissioners, competence of board commissioners and meeting frequency of board commissioners have significantly positive effect on financial distress.